2021
DOI: 10.3390/ijms222010990
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Based Immune Profiling Combined with Machine Learning Discriminates Psoriatic Arthritis from Psoriasis Patients

Abstract: Psoriasis (Pso) is a chronic inflammatory skin disease, and up to 30% of Pso patients develop psoriatic arthritis (PsA), which can lead to irreversible joint damage. Early detection of PsA in Pso patients is crucial for timely treatment but difficult for dermatologists to implement. We, therefore, aimed to find disease-specific immune profiles, discriminating Pso from PsA patients, possibly facilitating the correct identification of Pso patients in need of referral to a rheumatology clinic. The phenotypes of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Mulder et al. ( 30 ) aimed to detect disease-specific immune profiles from the phenotype of peripheral blood immune cells, which were effectively able to differentiate between psoriasis and psoriatic arthritis patients. Authors utilized a random forest-based algorithm coupled with in-depth flow cytometry and with an excellent AUC of 0.95 and found that psoriatic arthritis patients exhibited upregulated differentiated CD4+CD196+CD183-CD194+ and CD4+CD196-CD183-CD194+ T-cells, whereas CD196+ and CD197+ monocytes, memory CD4+ and CD8+ T-cell subsets and CD4+ regulatory T-cells were downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Mulder et al. ( 30 ) aimed to detect disease-specific immune profiles from the phenotype of peripheral blood immune cells, which were effectively able to differentiate between psoriasis and psoriatic arthritis patients. Authors utilized a random forest-based algorithm coupled with in-depth flow cytometry and with an excellent AUC of 0.95 and found that psoriatic arthritis patients exhibited upregulated differentiated CD4+CD196+CD183-CD194+ and CD4+CD196-CD183-CD194+ T-cells, whereas CD196+ and CD197+ monocytes, memory CD4+ and CD8+ T-cell subsets and CD4+ regulatory T-cells were downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that blood immune cell profiling approaches are a powerful tool for detailed characterization of immune cell subsets in peripheral blood of healthy individuals and patients ( 18 , 22 24 ). The association of peripheral immune cell changes and disease progression of type 1 diabetes has been shown in several studies, especially in newly diagnosed diabetes patients ( 6 , 7 , 23 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The NLP and genetic data were adopted in electronic medical records to identify 31 PsA‐related predictors and assess the risk of PsA 104,105 . Besides, other studies built ML models based on blood immune profiling and serum proteomics to discriminate between PsA and psoriatic patients 106,107 . Based on these models, a minimal disease activity (a clinical state characterized by low levels of disease activity) predictive model was developed, with the variables of global pain, impact of the disease (PsAID), patient global assessment of disease, and physical function (HAQ‐Disability Index) having the greatest predictive ability 108 .…”
Section: Ai Application In Psoriasis: Where We Are Nowmentioning
confidence: 99%
“…104,105 Besides, other studies built ML models based on blood immune profiling and serum proteomics to discriminate between PsA and psoriatic patients. 106,107 Based on these models, a minimal disease activity (a clinical state characterized by low levels of disease activity) predictive model was developed, with the variables of global pain, impact of the disease (PsAID), patient global assessment of disease, and physical function (HAQ-Disability Index) having the greatest predictive ability. 108 Besides PsA, patient records were detected to identify the top predictors of noncalcified coronary plaque burden in psoriasis, which included obesity, dyslipidemia, and inflammation factors.…”
Section: Preventive Medicinementioning
confidence: 99%